Social contexts of exclusionary reactions: study on Muslim and Christian relation in the city of Ambon - Cahyo Pamungkas (Indonesian Journal of Islam and Muslim Societies, 2015)
This study aims to answer the question of what social context related to atti- tudes of exclusionary reactions between Muslims and Christians. The data used in this research is resulted from interviews in the city of Ambon. The conceptual framework used to analyze findings of fieldwork is about relation- ship between ethno-religious identification and exclusionary reactions. In addition, actual or symbolic competition in the political, economic, social and cultural behaviour contributes to exclusionary attitudes. Likewise, the collective memory of the conflict led individuals to have prejudices against out-group members. Based on interview data, this study indicates that exclu- sionary reactions present in the city of Ambon in the form of social avoidance between Muslim and Christian students and the support for residential segre- gation. Both of these phenomena related to political and symbolic competi- tion in public institutions such as public universities. Also, social processes of implanting ethno-religious identity in their families have roles in the creation of prejudicial attitudes against out-group members. The collective memory of the conflict also contributes unto the phenomena of social avoidance and support for residential segregation. Studi ini bertujuan untuk menjawab pertanyaan konteks sosial apa yang berkaitan dengan meningkatnya fenomena eksklusivisme sosial antara umat Islam dan Kristen. Data yang digunakan sebagai basis untuk menjawab pertayaan ini tersebut berasal dari sejumlah wawancara di Kota Ambon. Kerangka konsep yang digunakan untuk menganalisis temuan lapangan adalah tentang hubungan identifikasi terhadap identitas kelompok etnik dan agama dengan perilaku mengecualikan kelompok lain. Selain itu, kompetisi aktual maupun simbolik dalam bidang politik, ekonomi, dan sosial budaya ikut memberikan kontribusi pada perilaku mengecualikan kelompok lain. Demikian juga memori kolektif mengenai konflik di masa lalu menjadikan seseorang memiliki prasangka terhadap kelompok lain yang berbeda agama dan suku. Berdasarkan data wawancara, penelitian ini menunjukkan bahwa perilaku mengekslusi kelompok agama atau etnik lain di Kota Ambon dalam dijumpai dalam bentuk fenomena menghindari kelompok lain dan keinginan untuk tinggal dalam lingkungan yang homogen. Kedua fenomena ini memilki hubungan dengan persaingan politik dan simbolik di lembaga-lembaga publik seperti perguruan tinggi negeri dan proses sosial menanamkan identitas agama dan etnik di dalam keluarga. Memori kolektif tentang konflik juga menyebabkan seseorang mendukung upaya untuk mengecualikan kelompok lain.